The sociology of warabandi: a case study from Pakistan - Merrey, Douglas J. (1986)
This paper uses a case study to address a fundamental issue in irrigation management: the relationship between technology and the organization required to use that technology productively. When an irrigation system is developed over time by a local community, the technology and the organization evolve together. However, when engineers design and construct large scale irrigation systems, there is a tendency to concentrate on the civil works, and to assume that, at least on the local level, whatever organization is required will evolve by itself. This was the assumption of the designers of the large irrigation systems built by the British and post colonial governments in present day Pakistan and the northwestern states of India.